Pembuatan Lampu Lava sebagai Pengaplikasian Ilmu Kimia secara Sederhana - Aina, Nur; Utomo, Setiyo (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LP2M), Universitas Mulawarman, 2024)
Chemistry is part of science which studies the changes that occur in matter and these properties. Where the application of chemistry or science can be found in everyday life. One of them is the manufacture of lava lamps which are used as a method of applying chemistry by studying the reactions that occur. Therefore, in the Real Work Lecture 49 program of Mulawarman University, individual work program activities are carried out, namely making lava lamps by utilizing tools and materials that can be found in everyday life as a simple application of chemistry. Collection of tools and materials to be used, preparing gifts for students as a form of appreciation, preparing materials and adding insight to students which will be displayed in the form of Power Point, carrying out individual work programs in grade 5 of State Elementary School 001 Samboja and delivering materials. The entire series of individual work programs went well and in accordance with the plans and needs of the students at Sekolah SD Negeri 001 Samboja.